A Framework to boost the potential of networkin- a-box solutions - Baena-González, José Carlos; Fortes-Rodríguez, Sergio; Peñaherrera-Pulla, Oswaldo Sebastián; Barco-Moreno, Raquel (My University, 2021)
The expected heterogeneous connectivity provided by the fifth generation mobile network (5G) implies a huge revolution in the telecommunication field. Here, virtualisation and software implementation of network elements have been positioned as a key elements for this revolution. At the same time and as a consequence of the evolution of these two paradigms, network-in-a-box solutions have also emerged as a potential way in the deployment of networks, offering a portable infrastructure. Here, this work presents a framework for easing the management tasks of the network-in-a-box devices, allowing abstracting the hardware and software implementation of these kind of solutions. We provide an experimental validation of the framework through the deployment of a portable cellular network. Besides, a Cloud Gaming service is launched on this scenario, showing the versatility and strengths that the framework provides to these novel solutions.
Keywords: Redes digitales de servicios integrados; Network in-a-box; Framework; Cloud gaming; Versatility